PENGARUH KEUNIKAN PRODUK, HARGA DAN PROMOSI TERHADAP KEPUTUSAN MEMILIH SEKOLAH MENENGAH KEJURUAN KESEHATAN HUSADA PRATAMA - Risma Eka desiyani; Lucky Dita Agustiansyah; Puspita Maelani (Valuasi : Jurnal Ilmiah Ilmu Manajemen dan Kewirausahaan, 2022)
The problem in this study is that students prefer public high schools and vocational schools due to various factors than other private schools, especially in SMKK HP. The purpose of this study is to find out the effect of product uniqueness, price and promotion on students' decisions in choosing SMKK HP. This type of research is descriptive research. Descriptive research is a type of research that provides an overview or description of a similar situation possible without any treatment of the object studied. The population of class X is 301 people and the sample is 170 people. Data analysis used is a double linear regression analysis technique with the influence of free variables on bound variables by 58.2%. The results showed that the uniqueness of produik, price and promotion had a significant effect on the decision to choose Husada Pratama Health Vocational High School, both partially and together